Marketing Mix Analysis at Sapphire Hotel Sumedang - Feryana, Ryan Kurniawan; Fadilah, Nurul (Journal of Bussines Management Basic, 2024)
The marketing mix at Sapphire Hotel Sumedang includes 7p (product, price, promotion and place, people, physical evidence, and process). The results of the marketing mix research at the Sapphire Hotel Sumedang show that the product dimension is reflected in product quality which is good, the price dimension is reflected in the pricing and price discounts which are quite good but not optimal in giving discounts, the place dimension is reflected in the location which is good and as expected, the dimensions promotion reflected in advertising, public relations, direct marketing is quite good but not optimal in promotion through social media, the people dimension is reflected in good customer service, the physical evidence dimension is reflected in good facilities, the need for additional facilities, the process dimension is reflected in communication already pretty good. Sapphire Hotel Sumedang to further increase the price discounts, increase sales promotions on social media and add facilities so as not to lose competitiveness with competitors